Determinants of assets profitability: differences due to activity sector and company size - Monte, Ana Paula (2016)
Knowing the determinants of the profitability of a company is crucial for management but also for policy-makers at regional and national level to adopt measures to promote regional development. The interior region of a mainland Portugal is facing some problems related to aging population, lack of opportunities for young people, depressed and weak economy, where it is necessary to take measures to strengthen the business environment and gain power of attractiveness. In this paper we use a unique, privately database with financial data (and some nonfinancial variables)of 1,024 enterprises headquartered in the interior north and center of mainland Portugal for the time period of 2006 to 2009 to answer to the research question: “The return on total net assets (ROA) is influenced by the size, location and the corporate activity sector?”. Applying a positivist quantitative approach by a descriptive analysis and inferential analysis through the Kruskal Wallis test, we tested three main hypotheses. Our results seem to indicate that the profitability of companies (as measured by ROA) is influenced by economic activity sector and localizations of the company (geographic region) but not by company size.